The proteomic landscape of sperm surface deciphers its maturational and functional aspects in buffalo - Batra, Vipul; Dagar, Komal; Diwakar, Maharana Pratap; Kumaresan, Arumugam; Kumar, Rakesh; Datta, Tirtha Kumar (Frontiers in Physiology, 2024)
Buffalo is a dominant dairy animal in many agriculture-based economies. However, the poor reproductive efficiency (low conception rate) of the buffalo bulls constrains the realization of its full production potential. This in turn leads to economic and welfare issues, especially for the marginal farmers in such economies. The mammalian sperm surface proteins have been implicated in the regulation of survival and function of the spermatozoa in the female reproductive tract (FRT). Nonetheless, the lack of specific studies on buffalo sperm surface makes it difficult for researchers to explore and investigate the role of these proteins in the regulation of mechanisms associated with sperm protection, survival, and function. This study aimed to generate a buffalo sperm surface-specific proteomic fingerprint (LC-MS/MS) and to predict the functional roles of the identified proteins. The three treatments used to remove sperm surface protein viz. elevated salt, phosphoinositide phospholipase C (PI-PLC) and in vitro capacitation led to the identification of N=1695 proteins (≥1 high-quality peptide-spectrum matches (PSMs), P<0.05, and FDR<0.01). Almost half of these proteins (N=873) were found to be involved in crucial processes relevant in the context of male fertility e.g., spermatogenesis, sperm maturation and protection in the FRT, and gamete interaction or fertilization, amongst others. The extensive sperm-surface proteomic repertoire discovered in this study is unparalleled vis-à-vis the depth of identification of reproduction-specific cell-surface proteins and can provide a potential framework for further studies on the functional aspects of buffalo spermatozoa.